Improved yield of solvent free enzymatic methanolysis of palm and jatropha oils blended with castor oil - E., Maleki; K., Aroua M.; N., Sulaiman N.M. (Applied Energy, 2013)
In this work, castor oil was blended with palm and jatropha oils to improve the yield of solvent-free enzymatic methanolysis reaction. Transesterification reactions were carried out with stoichiometric ratio of methanol to oil and using lipozyme TL IM as catalyst at 45 Â°C and 200 rpm for 24 h. By adding only 10 castor oil to the reaction medium a surge in the yield of methanolysis of jatropha oil was observed (i.e. from 21.9 to 65.5). Increasing the amount of castor oil to 20 raised the yield of methanolysis of jatropha oil to 78.3. Blending 50 castor oil with palm oil increased the yield of enzymatic methanolysis from 11.9 to 76.2. Mixing castor oil with jatropha and palm oils improved the yield of solvent free single-step methanolysis reaction to the higher amounts than the maximum theoretical yield of lipozyme TL IM (i.e. 67).